2013
DOI: 10.1111/jocs.12231
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Reoperation Due to Left Atrioventricular Valve Regurgitation After Previous Correction of Complete Atrioventricular Septal Defect

Abstract: Patients with severe LAVVR post-ICR of CAVSD may undergo reoperation with acceptable postoperative mortality and morbidity; however, they are at an increased risk for developing postoperative LAVVR and subsequent reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Different recent studies have reported a re-operation rate between 6.8% and 11% in patients with CAVSD undergoing twopatch or single patch technique correction (22). Other reported CAVSD series including both techniques failed to demonstrate statistically the single-patch technique as a possible predictor for early and late re-operation (1,22). Dividing the anterior bridging leaflet, affords an improved view of the margins of the defect, identifying carefully the true extent of the VSD through the atrium.…”
Section: The Management Of the Rvotmentioning
confidence: 99%
“…Different recent studies have reported a re-operation rate between 6.8% and 11% in patients with CAVSD undergoing twopatch or single patch technique correction (22). Other reported CAVSD series including both techniques failed to demonstrate statistically the single-patch technique as a possible predictor for early and late re-operation (1,22). Dividing the anterior bridging leaflet, affords an improved view of the margins of the defect, identifying carefully the true extent of the VSD through the atrium.…”
Section: The Management Of the Rvotmentioning
confidence: 99%
“…This impairment not only increases the risk of "reoperation", but also can increase the mortality rate and even the cost of hospitalization, by hemodynamic impairment [14,[27][28][29]. In addition, AVSD reveals a wide range of heart and non-cardiac diseases, so it requires careful preoperative examination and multiple surgical procedures with different treatment options.…”
Section: Issn 0970-938x Wwwbiomedresinfomentioning
confidence: 99%
“…In North America and Europe, between 9% and 17% of patients with complete atrioventricular septal defect (AVSD) are discharged home with significant residual left atrioventricular valve regurgitation (LAVVR) after definitive surgical repair, even with intraoperative monitoring by transesophageal echocardiography [ 1 , 2 ] . Aside from the obvious risk of reoperation that it implies, the presence of LAVVR with hemodynamic compromise in this period may increase length of hospital stay, morbidity and mortality, and it may also increase costs [ 1 - 6 ] .…”
Section: Introductionmentioning
confidence: 99%